Test of Moisture Content and Organolaptic Properties of Rabbit Meat Nuggets (Oryctolagus cuniculus) with The Addition Of Carrots (Daucus carota) - Yulianti, Icha Putri; Frasiska, Nurul; Wulansari, Putri Dian (Bulletin of Applied Animal Research, 2025)
The aim of this research was to determine the effect of adding carrots on water content and organoleptic tests in making rabbit meat nuggets. The materials used in this research were local rabbit meat, carrots and complementary ingredients consisting of cornstarch, garlic, ground pepper, salt, sugar, flavorings and eggs. The design used was a completely randomized design (CRD) with four treatments, each treatment consisting of five replications. The treatments given were P0 (80% rabbit meat + 0% carrots), P1 (80% rabbit meat + 10% carrots), P2 (80% rabbit meat + 15% carrots), P3 (80% rabbit meat + 20% carrots). ). The variables in this research include water content tests and organoleptic tests. Water content test data were analyzed using variance analysis (ANOVA). If the variance test shows a real difference, it will be continued with the Duncan Multiple Range Test and the data from the organoleptic test results will be analyzed using the Kruskal-Wallis test and the Mann-Whitney test. The results of this research show that there is a real effect of adding carrots on the water content, taste and panelists' preferences for rabbit meat nuggets. However, the aroma, texture and hardness showed no difference. The conclusion of this research is that the best addition of carrots in making rabbit nuggets is the P2 treatment, namely the addition of 10% carrots.